118k views
5 votes
Help, please! Thankyou!!!!

Help, please! Thankyou!!!!-example-1
User Adi Shavit
by
5.8k points

2 Answers

4 votes

Answer: C

Step-by-step explanation: simply apply the distributive property to each half of the expression to be left with terms that can be combined.

(8x + 16y)/2 = 4x + 8y

4(x - y) = 4x - 4y

(4x + 8y) + (4x - 4y) = 4x + 4x + 8y - 4y

= 8x + 4y => C

User Mingliang
by
5.1k points
6 votes

Answer:


(8x+16y)/(2)+4(x-y)=(2*4x+2*8y)/(2)+4*x-4*y\\\\=(2*(4x+8y))/(2)+4x-4y\\\\=4x+8y+4x-4y=8x+4y

Explanation:

User Zork Media
by
5.5k points